Activatory Receptor NKp30 Predicts NK Cell Activation During Controlled Human Malaria Infection - Walk, Jona; Sauerwein, Robert W. (Frontiers in Immunology, 2019)
Natural killer (NK) cells are known to be activated during malaria infection, exhibiting both cytokine production and cytotoxic functions. However, NK cells are heterogeneous in their expression of surface activatory and inhibitory receptors which may influence their response to malaria parasites. Here, we studied the surface marker profile and activation dynamics of NK cells during a Controlled Human Malaria Infection in 12 healthy volunteers. Although there was significant inter-patient variability in timing and magnitude of NK cell activation, we found a consistent and strong increase in expression of the activatory receptor NKp30. Moreover, high baseline NKp30 expression was associated with rapid NK cell activation already at low parasitemia. Our data suggest that NKp30 expression may influence the NK cell response to P. falciparum, explaining inter-patient heterogeneity and suggesting a functional role for this receptor in malaria.